Handling three regulatory elements in one transgene: combined use of cre-lox, FLP-FRT, and I-SceI recombination systems. (December 2005) - Rodin, Sergey; Georgiev, Pavel
Studies of regulatory systems in transgenic Drosophila are often compromised by possible genomic position effects on gene expression. As a result, it is desirable to be able to manipulate multiple regulatory elements in a single transgene construct. We developed an I-SceI endonuclease-based method to efficiently delete preassigned sequences from transgenes with the use of direct repeat sequences of just 126 nucleotides. This system can be used in combination with the existing cre-lox and FLP-FRT recombinational mechanisms in order to modify up to three regulatory regions in a given transgene. We validated the utility of our combination approach by demonstrating new properties of the Fab-7 insulator.